Creative individuals, "Kaya Bola" exceptionalism and sustainable development in twenty-first century Ghana - Ebenezer Owusu-Sekyere (Journal of Global Entrepreneurship Research, 2019)
This article pays attention to the activities of Kaya Bola (KBs)-informal waste collectors in Kumasi, Ghana whose imperatives are given little attention in the sustainable development narratives. How their activities illuminate good livelihood practices, proper city governance, and foster economic empowerment are discussed using multiple research methodologies. As the article shows, KBs have used their exceptional skills in waste collection to launch themselves into sustainable urban employment. They are intensely situated in the specifics of articulations and imbrications in many other processes. The most useful are that beyond keeping the city clean, they have also emerged as a campaign to combat joblessness, social exclusion, urban discontent, and spatial fragmentation associated with rigid labor arrangements under the neoliberal economic restructuring. The article contends that their image as unruly and messy is misleading. Contrary, their contribution toward the urban space calls for a recalibration of policies toward achieving the SDGs.
Keywords: 650; Ghana; Informal waste collectors; Kaya Bola; Sustainable development; Solid waste